Pills or Push-Ups? Effectiveness and Public Perception of Pharmacological and Non-Pharmacological Cognitive Enhancement - Caviola, Lucius; Faber, Nadira S. (Frontiers in Psychology, 2015)
We review work on the effectiveness of different forms of cognitive enhancement, both pharmacological and non-pharmacological. We consider caffeine, methylphenidate, and modafinil for pharmacological cognitive enhancement (PCE) and computer training, physical exercise, and sleep for non-pharmacological cognitive enhancement (NPCE). We find that all of the techniques described can produce significant beneficial effects on cognitive performance. However, effect sizes are moderate, and consistently dependent on individual and situational factors as well as the cognitive domain in question. Although meta-analyses allowing a quantitative comparison of effectiveness across techniques are lacking to date, we can conclude that PCE is not more effective than NPCE. We discuss the physiological reasons for this limited effectiveness. We then propose that even though their actual effectiveness seems similar, in the general public PCE is perceived as fundamentally different from NPCE, in terms of effectiveness, but also in terms of acceptability. We illustrate the potential consequences such a misperception of PCE can have.